PENERAPAN PENDEKATAN CREATIVE PROBLEM SOLVING (CPS) UNTUK MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS PESERTA DIDIK SMP - Elva Tati Susanti; Yayu Laila Sulastri (UJMES (Uninus Journal of Mathematics Education and Science), 2020)
The underlying problem of this research is the low ability of students in mathematical representation in learning mathematics. One alternative learning that can be applied to improve students' mathematical representation ability is the Creative Problem Solving (CPS) approach. The purpose of this study is to analyze the improvement of mathematical representation ability of students who learn using the Creative Problem Solving (CPS) approach with students learning to use the expository method. This study uses a quasi-experimental method with the nonequvallent pretest and posttest group control design. The study was conducted in one of the junior high schools in Bandung Regency. The population in this study were all students with samples namely class VII A (experimental class) and VII B (control class). The research data obtained from the use of instruments in the form of mathematical representation ability tests and questionnaire responses of students. The results of the analysis show that: 1) Increasing the mathematical representation ability of students who get learning using the Creative Problem Solving (CPS) approach is better than students who get learning with the expository method, 2) Students' responses to learning using the Creative Problem Solving approach (CPS) positive.